Implementation of Forward Chaining Method in Expert System to Detect Diseases in Corn Plants in Muara Tami District - Elvis Pawan; Rosiyati M.H Thamrin; Widodo Widodo; Sariaty H.Y.Bei Sariaty H.Y.Bei; Junus J. Luanmasa (International Journal of Computer and Information System (IJCIS), 2022)
Diseases in plants are very disturbing and hinder to obtain maximum yields, corn plants are plants that are very easy to attack by diseases or pests, so expertise is needed in dealing with corn plant diseases. Problems arise when farmers do not have the ability and expertise to detect early corn plant diseases as experienced by farmers in the mura tami district. This study aims to design an expert system application as a form of solution for farmers so that they can detect plant diseases as early as possible. The expert system was developed using the forward chaining method which is a forward trace method. System development using the PHP programming language and mysql database. The results of this study conclude that the forward chaining method is suitable to be implemented in an expert system. The test results using the black box method stated that 100% of the system's functionality could work well, while testing using the user acceptance test (UAT) method stated that 84% of respondents strongly agreed that the application was implemented.